Plants play a crucial role in the development of soil fungal communities in the remediated substrate after EDTA washing of metal-contaminated soils - Maček, Irena; Pintarič, Sara; Šibanc, Nataša; Rajniš, Tatjana; Kastelec, Damijana; Leštan, Domen; Suhadolc, Marjetka (Frontiers in Environmental Science, 2022)
In this study, we investigated the importance of plant cover for secondary succession and soil fungal community development in the remediated substrates after EDTA washing of metal-contaminated soils. The abundance of the total fungal community, determined by ITS fungal marker genes (Internal Transcribed Spacer region), and the root colonisation with arbuscular mycorrhizal (AM) fungi were monitored in two types of soil material (calcareous and acidic) seeded with perennial ryegrass (Lolium perenne L.) and without plant cover (bulk soil). Four months after the start of the experiment, the abundance of ITS genes in the soil clearly showed that the presence of plants was the main driver of the total fungal community, which increased in the rhizosphere soil in most treatments while it remained at a low level in the bulk soil (without plants). Interestingly, the addition of environmental inoculum, i.e. rhizosphere soil from a semi-natural meadow, had no positive effect on the abundance of the total fungal community. While fungal ITS genes were detected in soils at the end of the first growing season, arbuscular mycorrhizal (AM) structures were scarce in Lolium roots in all treatments throughout the first season. However, in the second season, more than one year after the start of the experiment, AM fungal colonisation was detected in Lolium roots in virtually all treatments, with the frequency of colonised root length ranging from 30% to >75% in some treatments, the latter also in the remediated soil. This study demonstrates the importance of plant and rhizosphere in the development and secondary succession of fungal communities in soil, which has important implications for the revitalisation of remediated soil and regenerative agriculture.